Banking in Germany : a short practical guide for the foreign banker by Martin Peltzer and Karl Nebendorf - Peltzer, Martin; Nebendorf, Karl (Frankfurt (am Main) : Knapp, 1973)
This book provides the international businessman - in particular for the foreign banker - with an English language summary of the German banking system in a condensed but precise form.
English and German.
osc 28/3/18
Loans
Keywords: Banks and banking; Banking law; Banks and banking, Foreign